Limitations of litigation as a tool for achieving social change: A perspective on South African and Zimbabwean litigation environment - Sigwegwe, Dumolwethu (University of the Witwatersrand, Johannesburg, 2024)
This research report seeks to investigate and analyse the limitations of using litigation as a tool for achieving social change in the legal environments of South Africa and Zimbabwe, with a particular focus on relevant provisions in the Constitutional framework. In other words, I consider how litigation related to socioeconomic rights, with a particular focus on the right to healthcare, has been limited in its capacity to bringing about societal transformation. Juxtaposing these legal systems should highlight the opportunities and challenges of utilising litigation. In South Africa the 1996 Constitution, and in Zimbabwe the 2013 Constitution play a significant role in shaping socio-economic rights, enhancing access to justice, and promoting social transformation. Further, the Bill of Rights and the Constitutional Court all contribute to the potential effectiveness of litigation. Relying on the Constitutional framework, literature concerning the effectiveness and critique of litigation, and case studies from South Africa and Zimbabwe the article illustrates the potential and shortfalls of litigation in advancing socio- economic rights. The argument highlights that litigation has made substantial advancements in effecting systemic and policy changes, as well as in holding governments accountable. However, it also emphasizes the existence of potential obstacles, such as the failure to implement court orders, institutional barriers, and structural or procedural issues that require addressing in the pursuit of societal transformation. The research report concludes that whilst litigation can be seen as just one tactic in the repertoire for challenging societal and systemic injustices, it must however, be complemented with a broad range of strategies that include advocacy, grassroots movements, and policy reform, to address the complex underlying causes of social issues effect social change in South Africa and Zimbabwe
A research report submitted in fulfillment of the requirements for the Master of Laws, In the Faculty of Faculty of Commerce, Law and Management, School of Law, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Litigation; Social change; Socio-economic rights; Right to healthcare; South Africa; Zimbabwe; SDG-17: Partnerships for the goals